2017
DOI: 10.3347/kjp.2017.55.6.673
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Dirofilaria immitis in Cats from Liaoning Province, Northeastern China

Abstract: The present study was performed to investigate the seroprevalence and risk factors for Dirofilaria immitis infection in cats from Liaoning province, northeastern China. From October 2014 to September 2016, sera of 651 cats, including 364 domestic cats and 287 feral cats (332 females and 319 males) were assessed. They were tested for the presence of D. immitis antigen using SNAP Heartworm RT test kit. In this population, the average prevalence was 4.5%. Age and rearing conditions (feral or domestic) were found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
0
4
1
Order By: Relevance
“…Montoya-Alonso et al (24) reported that sex is influential on the prevalence of D. immitis in cats (P < 0.001) and in this study the prevalence of the disease is higher in male cats than females. On the other hand, some other reports suggest that sex has no significance for the prevalence of the disease, yet nevertheless indicate a higher prevalence in male cats (17,23). The present study also demonstrated that sex has no significance for the prevalence of dirofilariasis in cats.…”
Section: Tab 1 Seropositivity Rates For Dirofilariasis In Cats In Dcontrasting
confidence: 62%
See 1 more Smart Citation
“…Montoya-Alonso et al (24) reported that sex is influential on the prevalence of D. immitis in cats (P < 0.001) and in this study the prevalence of the disease is higher in male cats than females. On the other hand, some other reports suggest that sex has no significance for the prevalence of the disease, yet nevertheless indicate a higher prevalence in male cats (17,23). The present study also demonstrated that sex has no significance for the prevalence of dirofilariasis in cats.…”
Section: Tab 1 Seropositivity Rates For Dirofilariasis In Cats In Dcontrasting
confidence: 62%
“…Similar to these reports, the present study revealed no relation between the age of the animals and the prevalence of the disease. On the other hand, the prevalence of the D. immitis has been reported to significantly increase with advanced age in cats (17) and in dogs (5). Differently, although statistically insignificant, Magi et al (22) reported a higher prevalence in 1 to 2 year old cats, compared to older cats, which is in agreement with the results of the our study.…”
Section: Tab 1 Seropositivity Rates For Dirofilariasis In Cats In Dmentioning
confidence: 99%
“…In the direct blood examination, 1-2 drops of the blood sample were placed between a slide and a coverslip. The slides were examined under a microscope, and microfilariae were in cats are reported in many countries in Asia, Africa, Europe, and America (10,13,20,25,30). In studies conducted in different parts of Europe, the prevalence of the disease was 9.4% (3/32) in Greece, 4.8% (32/62) in Italy, 3.5% (5/141) in Portugal, and 24.40-25.20% (61-63/250) in Spain (6,10,25,38).…”
Section: Resultsmentioning
confidence: 99%
“…Although D. immitis is most commonly found in dogs in China, the level of D. immitis infection in cats should also be taken into consideration. A study reported D. immitis prevalence of 3.0% in cats in Gansu, northwestern China [ 6 ], Kang et al [ 24 ] reported 1.9% prevalence in stray cats from Liaoning, Jilin, Heilongjiang, and Shandong, and another study reported an average prevalence of D. immitis of 4.5% in cats in Liaoning [ 17 ]. The overall prevalence of antibody-positive cats was found to be 6.7% in Taiwan in 2017 [ 33 ].…”
Section: Discussionmentioning
confidence: 99%